Quasi-hyperbolic time preferences and their intergenerational transmission - Fabian Kosse; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This study explores the intergenerational transmission of time preferences and focuses on the question which specific aspects of mother's time preference are related to her preschool child's ability to delay gratification. We provide a new procedure for assessing the parameters of a 'quasi-hyperbolic' discount function (Laibson, 1997) using two trade-off experiments. We apply the procedure to a sample of 213 mother-child pairs and show that especially mother's beta parameter is related to her preschool child's ability to delay gratification.
urn:nbn:de:bsz:180-madoc-330033
Keywords: D90; D10; 330; Intergenerational Transmission; Time Preference; Quasi-Hyperbolic Discounting; Preschool Children